Design and Simulation of a Microcontroller-Based Class D Power Amplifier for Piezo-electric Actuators in Bone ConductionHearing Aids - Remnesjö Bergstrand, Albin; Johansson, Emil (My University, 2025)
Conventional linear audio power amplifiers have been and continue to be popular in audio applications. In recent years, digital Class D switching power amplifiers have increased in popularity, as the demand for smaller and more efficient electronic devices has surged. Continuous technological advances have further improved audio quality and allowed for smaller and more efficient Class D amplifiers. One audio technology that uses Class D amplifiers is bone conduction hearing aids. These systems generally consist of an extrinsic microphone and sound processor, connected to a percutaneous device with the purpose of generating sound through vibrations to the skull bone. Historically, bone conduction devices have been designed and operated based on electromagnetic principles using electromagnetic actuators. Over time, a more efficient type of actuator is increasing in popularity, one that utilizes the piezoelectric force. Low-voltage Class D amplifiers are often only available in integrated circuits (ICs), which take a long time to develop and can be a bottleneck in the process. This thesis explores an alternative approach by developing a design and simulation framework for a low-voltage Class D power amplifier using discrete components to drive a piezoelectric actuator load. The following approach aims to reduce the development time while showcasing the feasibility of constructing low-voltage Class D power amplifiers utilizing discrete components for piezoelectric actuator loads, achieving performance comparable to integrated solutions. A Class D amplifier, using a H-bridge power stage, with ΔΣ to BD PWM with dead-time control, has been developed in simulation and with PCB design. The amplifier, operating across the audio frequency range (20 Hz to 20 kHz), achieved a peak SNR of 69.32 dB and a THD+N peak of 0.15% when driven with a 0.658 VRMS sinusoidal input with a fundamental frequency of 4410 Hz. A peak apparent efficiency of 86.4% was observed with an input voltage of 2.44 VRMS. Compared to IC designs reported in technical literature and found in commercial products, the results are promising. Thus, the conclusion is that the idea of designing a low-voltage discrete Class D amplifier for piezoelectric hearing aids is deemed viable. Still, its performance could be greatly improved by incorporating gate drivers, a higher-order ΔΣ modulator, and more refined filter designs.
Keywords: Bone conduction, hearing aid, piezoelement, sigma Delta, Class D amplifier